Thematic exploration of Slovenia’s path to independence in Slovenian Scopus-indexed history journals - Hazemali, David (Annales. Series historia et sociologia, 2024)
This article explores how Slovenian history journals have portrayed Slovenia’s path to independence. The analysis of 3,759 articles and other journal contributions from 12 Scopus-indexed journals, using select digital humanities tools and methods, reveals that themes concerning Slovenia’s path to independence, though less frequent overall, exhibit a dynamic pattern of regular occurrence, influenced by commemorations and special issues of journals. This suggests growing scholarly interest over time. The analysis identified four key thematic groups: Socio-cultural, Political, Religious, and Yugoslavia themes. Furthermore, metadata analysis indicates a balanced distribution of male and female first authors and equitable thematic accessibility across publication languages. These findings contribute to a nuanced understanding of how Slovenian Scopus-indexed history journals engage with this critical topic.
Keywords: bibliometric and sociometric analyses; bibliometrične in sociometrične analize; content analyses; democratization processes; demokratizacijski procesi; digital humanities tools and methods; independent Slovenia; orodja in metode digitalne humanistike; samostojna Slovenija; Slovenian history journals; slovenske zgodovinske revije; vsebinske analize; zgodovinske revije